Integrated people-centered eye care: A scoping review on engaging communities in eye care in low- and middle-income settings. - Ling Lee; Elise Moo; Tiffany Angelopoulos; Aryati Yashadhana (PLoS ONE)
Background Community engagement has been endorsed as a key strategy to achieving integrated people-centered eye care that enables people and communities to receive a full spectrum of eye care across their life-course. Understanding the ways communities are engaged in eye care, to what degree participation is achieved, and the factors associated with intervention implementation is currently limited. Objective The scoping review aimed to assess how community engagement is approached and implemented in eye care interventions in low- and middle-income countries, and to identify the barriers and facilitators associated with intervention implementation. Methods Searches were conducted across five databases for peer-reviewed research on eye care interventions engaging communities published in the last ten years (January 2011 to September 2021). Studies were screened, reviewed and appraised according to Cochrane Rapid Reviews methodology. A hybrid deductive-inductive iterative analysis approach was used. Results Of 4315 potential studies screened, 73 were included in the review. Studies were conducted across 28 countries and 55 targeted populations across more than one life-course stage. A variety of community actors were engaged in implementation, in four main domains of eye care: health promotion and education; drug and supplement distribution and immunization campaigns; surveillance, screening and detection activities; and referral and pathway navigation. With the approaches and level of participation, the majority of studies were community-based and at best, involved communities, respectively. Involving community actors alone does not guarantee community trust and therefore can impact eye care uptake. Community actors can be integrated into eye care programs, although with varying success. Using volunteers highlighted sustainability issues with maintaining motivation and involvement when resources are limited. Conclusion This scoping review provides researchers and policy makers contextual evidence on the breadth of eye care interventions and the factors to be considered when engaging and empowering communities in integrated people-centered eye care programs.